Canopy structure and theoretical coefficient of extinction in genotypes of arabic coffee in Colombia - Carlos Andres Unigarro Muñoz; Alvaro Jaramillo Robledo; Lizardo Norbey Ibarra Ruales; Claudia Patricia Flórez Ramos (Acta Agronómica)
The canopy structure has a marked effect on the interception of the solar radiation and the plant photosynthesis, in addition to other processes that in their group, are the result of the plant-environment interaction. The present research was carried out at the Central Station Naranjal of CENICAFÉ (National Coffee Research Center - Chinchiná, Caldas, Colombia) in 25 genotypes of Coffea arabica L. which were divided in two groups. The first one with tall aspect plants (3.6 years old) and the second one, with short plant aspect (2.6 years old) both planted in a density of 5000 plants.ha-1. The leaf and branches angles distribution in the canopy were characterized in the different assessed genotypes, also the theoretical extinction coefficients for direct and diffuse solar radiation were estimated. In genotypes of high aspect, the plagiophile and spherical leaf distribution predominated, as in the ones of short aspect the planophile did. The parameter x, represents the ellipsoidal distribution of the leaf angles, which varied between 0.09 and 2.21 for genotypes of high aspect (vertical and spherical) and between 1.90 and 3.98 for the ones of short aspect (horizontal). The theoretical coefficients of extinction for the direct radiation derived of the parameter x varied between 0.63 to 0.83 for the group of high aspect, and the short one, showed values between 0.84 to 0.93, for the diffuse radiation the coefficients showed the same trend but with minor values. As regards the inclination angles of the branches was characterized for being planophile predominant.